ASSESSMENT OF STRENGTH COMPLIANCE WITH STANDARDS FOR TANZANIA EUCALYPTUS WOOD POLES TREATED WITH COPPER-CHROMIUM-ARSENIC COMPOUNDS - Mrema, Alex Lyatonga (Tanzania Journal of Engineering and Technology, 2018)
Samples of copper-chromium arsenic compounds (CCA) treated Eucalyptus poles for power transmission were sampled from a lot following Military Standard MIL-STD 105D, Single sampling, Tightened Inspection, Acceptable Quality Level (AQL) of 4 as provided for in the South African Standard SABS 754:1994 from lots containing 151-500 poles. Samples were randomly selected from a lot. Maximum fiber stresses were evaluated taking into account the actual taper in each pole. The cantilever loading test was performed on the samples following SABS 754:1994. It was found out that the average taper for the poles was smaller than that assumed in the standard due to the different pole growth characteristics and environment in Tanzania and that the average modulus of elasticity obtained for the poles was lower than the average assumed in SABS 754:1994. The poles also showed excessive deflections at working loads. It is recommended to the Tanzania Bureau of Standards that although SABS 754:1994 is meant to be used for eucalyptus poles grown in Southern Africa south of the Sahara that are treated with creosote or CCA there is a need to review it to take into account the actual characteristics of the poles grown in Tanzania where they are normally grown in highland areas with higher rainfall and colder climates.